2020
DOI: 10.1038/s41433-020-0836-x
|View full text |Cite
|
Sign up to set email alerts
|

Neurodegeneration in Alzheimer’s disease and glaucoma: overlaps and missing links

Abstract: The eye is said to be the window into the brain. Alzheimer’s disease (AD) and glaucoma both being diseases of the elderly, have several epidemiological and histological overlaps in pathogenesis. Both these diseases are neurodegenerative conditions. Over the years, a consensus has developed that both may be two ends of a singular spectrum of diseases. Epidemiological studies have shown that more Alzheimer’s patients may be suffering from glaucoma than general healthy population. Retinal ganglion cell damage is … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
36
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(38 citation statements)
references
References 111 publications
1
36
0
1
Order By: Relevance
“…Patients who have glaucoma and AMD have been associated with an increased risk for AD [ 15 ]. Similarly, AD patients have an increased prevalence for glaucoma with glaucoma observed in 7–24% of AD patients in comparison to 4–10% of healthy controls [ 16 ]. Advanced AMD prevalence was also doubled in AD patients in comparison to controls.…”
Section: Introductionmentioning
confidence: 99%
“…Patients who have glaucoma and AMD have been associated with an increased risk for AD [ 15 ]. Similarly, AD patients have an increased prevalence for glaucoma with glaucoma observed in 7–24% of AD patients in comparison to 4–10% of healthy controls [ 16 ]. Advanced AMD prevalence was also doubled in AD patients in comparison to controls.…”
Section: Introductionmentioning
confidence: 99%
“…Bei der glaukombedingten Neurodegeneration werden auf molekularer Ebene ähnliche Mechanismen vermutet wie bei chronischen neurodegenerativen Erkrankungen des zentralen Nervensystems, z. B. der Alzheimer-Erkrankung [ 45 ]. Experimentelle Studien an retinalen Zellkulturen und Tiermodellen (chronisch erhöhter IOD, RGZ-Axotomie, Sehnerv-Crush-Modell) weisen darauf hin, dass bei dem glaukomatösen RGZ-Verlust neben dem Augeninnendruck verschiedene Ursachen wie Exzitotoxizität, oxidativer Stress, gestörter axonaler Transport mit Mangel an neurotrophen Faktoren, mitochondriale Dysfunktion und autoimmune Dysregulation involviert sind [ 1 ].…”
Section: Pathogenese Der Glaukomerkrankungunclassified
“…I read with great interest the article recently published in Eye by Sen et al [1]. The authors nicely reviewed overlaps and missing links between Alzheimer's disease (AD) and glaucoma, and concluded that several factors point toward a common pathogenesis at some level for both diseases.…”
Section: To the Editormentioning
confidence: 99%